2012
DOI: 10.1142/s1088424612500812
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling the artificial special pair to slow down the rate of singlet energy transfer

Abstract: Nature has designed efficient photosystems allowing microorganisms such as photo-bacteria to survive under particularly difficult environment due to scarcity of light [1]. In the photosynthetic membranes of these organisms, exciton (energy excitation migration), energy and electron transfers occur with impressing rates [1], and numerous research groups around the world attempted to design chemical models, which were recently reviewed by us [2]. One of the key components in both the natural and synthetic system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Their amplitude (∼6.2 × 10 9 s −1 ) is similar to that recently reported for compound 14 (11 × 10 9 s −1 ; Figure 4) using time-resolved femtosecond transient absorption spectroscopy. 30 The larger global k ET (S 1 ) value for 14 over 10a,b is fully consistent with the shorter D•••A 1 separation for the former (distance C meso •••C meso = 4.98 Å for anthracenyl, 6.30 Å for DPS). 28 Consequently, D is closer to both A 1 and A 2 .…”
Section: ■ Introductionsupporting
confidence: 59%
“…Their amplitude (∼6.2 × 10 9 s −1 ) is similar to that recently reported for compound 14 (11 × 10 9 s −1 ; Figure 4) using time-resolved femtosecond transient absorption spectroscopy. 30 The larger global k ET (S 1 ) value for 14 over 10a,b is fully consistent with the shorter D•••A 1 separation for the former (distance C meso •••C meso = 4.98 Å for anthracenyl, 6.30 Å for DPS). 28 Consequently, D is closer to both A 1 and A 2 .…”
Section: ■ Introductionsupporting
confidence: 59%
“…5), for which S 1 energy transfers were clearly established [11,36]. Efficient energy transfer are generally accompanied by a strong fluorescence quenching of the donor, clearly felt by the significant decrease in F F and lifetime, t F , and the close resemblance between the excitation and absorption spectra of the dyad or polyad.…”
Section: Electronic Spectramentioning
confidence: 89%
“…A recent investigation indicated that faster rates of S 1 energy transfers were accompanied by stronger MO couplings between the acceptor and the donor (see compound 4 for example) [36]. Coupling is defined by atomic orbital distribution that is spread over 2 or more porphyrin macrocycles.…”
Section: Molecular Orbital Analysismentioning
confidence: 99%
“…This concept led to the idea of MO couplings and decoupling based on the proximity of the chromophores, which was also experimentally verified using comparison of k ET versus representations of the frontier MOs. 36 For compound 6, the donor fluorescence was not detected, meaning that the antenna fluorescence was completely quenched and that the rate for energy transfer must be very fast. Fortunately, the fs transient absorption spectra exhibited stimulated fluorescence (see the strong negative signal in Fig.…”
Section: Fig 25 Structures Of the Dendrimers 3(m)-g X Investigated Inmentioning
confidence: 99%
“…Representation of the frontier MOs of 6. Image modified from Harvey et al 36 and reproduced with permission from World Scientific. in (monporphyrin donor)−C 6 H 4 −(monoporphyrin acceptor)) also indicated a discrepancy where again the cofacial systems exhibit slower rates from severalfold to one order of magnitude difference.…”
Section: Fig 25 Structures Of the Dendrimers 3(m)-g X Investigated Inmentioning
confidence: 99%